Identifying acoustic correlates of stress in Malay words - Wan Ahmad, Wan Aslynn Salwani (Universiti Putra Malaysia Press, 2019)
The prosodic characteristic of Malay, spoken in Malaysia, such as stress and rhythm, are understudied instrumentally. Most of the studies reported are based on auditory and perceptual observations. This study looks at the acoustic correlates of stress in Malay words in terms of its different types of morphological structures and number of syllables. To investigate this, a list comprising a) disyllabic monomorphemic words; b) polysyllabic monomorphemic words and c) polysyllabic morphologically complex words in isolation and in sentence was created. Three Malay native speakers were recruited as language informants. The measurements of the vowel durations and intensity of those target words, produced by the speakers, were then elicited from the spectrograms and analysed statistically. The findings show that: a) for vowel duration; word final lengthening is only prominent feature in both disyllabic and polysyllabic monomorphemic isolated words, whereas stem-final lengthening is found for polysyllabic monomorphemic complex words in isolation; b) for the normalised intensity, only the results for disyllabic monomorphemic target words are found to be significant, in which V1 is louder than V2. However, no other significant effects of vowel position, production type, subjects and morphological contexts are found on the normalised intensity. From this data, it can be proposed that intensity is not a robust indicator of stress in Malay. A correlation test run on these two phonetic variables also revealed no relationship between the vowel duration and the normalised intensity. This experiment indicates that words produced in isolation did show alignment of prosodic prominence with particular syllables, akin to what has been found in studies of lexical stress in other languages but, in connected speech, this alignment seem to disappear.